2001
DOI: 10.1002/jnr.1136.abs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osmotic stress on potassium accumulation around glial cells and extracellular space volume in rat spinal cord slices

Abstract: In rat brain and spinal cord slices, the local extracellular accumulation of K(+), as indicated by K(+) tail currents (I(tail)) after a depolarization step, is greater in the vicinity of oligodendrocytes than that of astrocytes. It has been suggested that this may reflect a smaller extracellular space (ECS) around oligodendrocytes compared to astrocytes [Chvátal et al. [1997] J. Neurosci. Res. 49:98-106; [1999] J. Neurosci. Res. 56:493-505). We therefore compared the effect of osmotic stress in spinal cord sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
3
8
1
Order By: Relevance
“…These detailed results have been supported by several studies that used a more limited range of osmotic variation (11, 147, 299, 369, 401) (Table 5). A study (166) on the CA3 region of the rat hippocampus at age P5 noted that α changed from 0.41 to 0.17 while λ increased from 1.38 to 1.49 after exposure to 215 mosmol kg −1 solution (Table 5).…”
Section: Tma-diffusion Measurements In Cns Tissuesupporting
confidence: 65%
See 1 more Smart Citation
“…These detailed results have been supported by several studies that used a more limited range of osmotic variation (11, 147, 299, 369, 401) (Table 5). A study (166) on the CA3 region of the rat hippocampus at age P5 noted that α changed from 0.41 to 0.17 while λ increased from 1.38 to 1.49 after exposure to 215 mosmol kg −1 solution (Table 5).…”
Section: Tma-diffusion Measurements In Cns Tissuesupporting
confidence: 65%
“…To study the effects of cell swelling on the [K + ] e changes evoked by a depolarizing pulse, 50 mM K + or hypotonic solution was applied. These maneuvers led to an increase in evoked [K + ] e that was much greater in the vicinity of astrocytes than near oligodendrocytes (66, 401). These results indicate that swelling is more pronounced in astrocytes than in oligodendrocytes, and suggests that astrocytes are responsible for the majority of the cell volume changes seen in nervous tissue (66).…”
Section: The Brain Cell Microenvironmentmentioning
confidence: 99%
“…This is a requirement because one of the best-documented functions of astrocytes, potassium homeostasis seems to involve an increase of cell volume (Walz and Juurlink, 2002). There is not nearly as much known about volume regulation in oligodendrocytes as in astrocytes, despite the fact that the extracellular space around oligodendrocytes is more compact than the one around astrocytes (Vargova et al, 2001). Oligodendrocytes should therefore exhibit larger changes in extracellular osmolarity than astrocytes during normal and pathological functioning.…”
Section: Volume Controlmentioning
confidence: 99%
“…To study the changes in K + flux and accumulation in the vicinity of the glial membrane during cell swelling, spinal cord slices were exposed to hypotonic stress (see also Vargová et al, 2001). In astrocyte‐like cells during the application of 200 mmol/kg for 20 min, the reversal potential evoked by a depolarization pulse rose by 17.2 ± 1.8 mV (n = 5; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The application of Ba 2+ almost completely blocked the decaying component of the inward and outward currents, as well as tail currents after depolarizing and hyperpolarizing voltage steps, indicating that these currents are carried predominantly by K + (Berger et al, 1991; Chvátal et al, 1995). Further analysis of oligodendrocyte currents in brain slice preparations (Chvátal et al, 1997, 1999; Vargová et al, 2001) revealed that I tail observed after the offset of a depolarizing pulse are caused by the reversed shift of K + across the cell membrane from the ECS into the cell. Because the glial membrane is highly permeable for K + , the membrane potential (V m ) is close to the reversal potential (V rev ) determined by the gradient of K + outside and inside the cell according to the Nernst equation.…”
mentioning
confidence: 99%